ANALISA KASUS KEJAHATAN SIBER DENGAN MENGGUNAKAN VISUALISASI DATA - Farrah Meirisah; Tata Sutabri (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
The development of information technology is currently growing rapidly. There are many ways to do visualization analysis. As with using tools that are widely spread, in this case the researcher aims to visually analyze data on cyber crimes that are rife in society. By conducting this evaluation, it is hoped that it can help related parties to overcome and prevent cybercrime in the community. The results of this study will be interesting results because they visually display data that is easy to read and easy to carry out an analysis in making decisions. Based on the results of the research, the researchers translated cybercrime into visual data form, based on the results of the research it is known that cybercrimes often occur in 2020, then the most common method of attack is hacked, finally the companies that are most often affected by cybercrime are companies engaged in the field of medical.